Projovem urbano: desafios, perspectivas e implicações de uma política pública na constituição dos saberes discentes - Sá, Roselene Moura de (2013)
The Public policy Projovem Urban was established by the Federal Government in order to democratize access to education for young people between 18 and 29 years, who don’t completed primary education. On this way, the Government decrease the rate of distortion of schooling. In view of the challenges, present in the complexity of relationships between young people and the school, will be made a indagation about the knowledge acquired in education through this program. Based on this restlessness, this study aimed to analyzing the knowledge which enables the Urban Projovem offers for the young in a public school in Fortaleza (Ceará). To achieve this objective, we defined the following specific objectives: to discuss the proposal of the Urban Projovem, aimed at understanding the educational process of young people in this program; identify what motivates young people to pursue education occasioned by Projovem Urban and investigate knowledge constituted in Urban Projovem that contribute to the formation of critical youth. The method chosen for this research, is the historical and dialectical materialism, with support in the qualitative approach, setting up to work with the case study. The empirical study was conducted in a school from teaching Fortaleza, located in the neighborhood of New Mondubim, 2011-2013. The bibliographic study that underlies this essay featured authors Arroyo, Coll, Dayrell, Freire, Telles, Martins, Nóvoa, Perrenoud, Pepper and Tardif. We selected seven teachers and 20 students as subjects of this research program. We adopted the following procedures for gathering information: literature review, participant observation, field diary, questionnaires characterization of teachers and students, and conducting semi-structured interviews. The following categories in this research were instituted: public policy, Urban Projovem, youths and students knowledge. The study results showed that the young members of the classrooms Projovem Urban aspire to transpose the lost time and complete their education, aiming a diploma to enter into the labor market in order to acquire improvements and facilities necessary for their survival. This program develops a learning transposing content, supporting its proposed teaching mediated integration teacher-student. The student learning occurs by means of prior knowledge of their existence, their expectations towards life, his tastes, cultures and emotions. The young are subjected to different contents that connect among themselves and with their lives, aiming reflections and changes in attitudes towards the challenges of their reality. In addition, the young elaborate knowledge who articulate with their realities, such as the conception of rights and duties of citizenship, and still reflect critically on their social perspective transformation, detect problems of their community, positioning here self to demand changes, learn the values of solidarity and mutual respect, establish projects to enter into the world of work, develop the autonomy in the face of studies, establishing itself as the need for lifelong learning.